Analisis Wacana Kritis Sosial Dalam Lagu “Surat Buat Wakil Rakyat Karya Iwan Fals” - Dinda Juwita; Aliasan .; Jufrizal . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Using a Critical Discourse Analysis (CDA) approach, this study will investigate the social criticism discourse found in Iwan Fals' song "Surat Buat Wakil Rakyat." This song was chosen because it reflects the voice of the people expressed in clear, satirical language and confronts power. This study uses a qualitative methodology with a descriptive approach. The lyrics of the song "Surat Buat Wakil Rakyat" are the main data source analyzed, and additional data are obtained from journals, literature, and othersources related to the theory of Critical Discourse Analysis. The analysis is carried out by identifying the text structure, discursive techniques, and social elements in the song's lyrics. This study found that this song contains criticism of people's representatives who are considered to have violated their mandate, often ignore people's expectations, and are trapped in political interests and power. In a social context, this song shows people's dissatisfaction with the current government and functions as a form of symbolic resistance through the medium of music. Consequently, the song "Surat Buat Wakil Rakyat" functions not only as a work of art but also as a tool to convey social criticism that pays attention to the power relationship between the people and the government.